2013
DOI: 10.1002/cctc.201200742
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐Assisted Ethanol Reduction as a New Method for the Preparation of Highly Active and Stable CNT‐Supported PtRu Electrocatalysts for Methanol Oxidation

Abstract: Highly active and stable PtRu nanocatalysts supported on carbon nanotubes were prepared by microwave‐assisted ethanol reduction in an ethanol/water mixture (1:1 v/v). During the reduction process, the presence of water is necessary for fast and substantial metal ion reduction. The prepared catalysts were characterized with inductively coupled plasma (ICP‐ES), TEM, XRD, and electrochemical techniques to investigate their structural properties and electrocatalytic activities. ICP analysis confirms the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…Recently, microwave‐enhanced catalytic reactions have aroused tremendous attention as they show a drastic acceleration of the catalytic reaction rate and selectivity under mild conditions . Furthermore, some chemical transformations that are impossible in the CRM can be performed successfully under the microwave reaction mode .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, microwave‐enhanced catalytic reactions have aroused tremendous attention as they show a drastic acceleration of the catalytic reaction rate and selectivity under mild conditions . Furthermore, some chemical transformations that are impossible in the CRM can be performed successfully under the microwave reaction mode .…”
Section: Introductionmentioning
confidence: 99%
“…The microwave technique has been applied to heterogeneous catalysis research in the past decade. [20][21][22][23][24][25][26][27][28][29][30][31][32] There are some studies that use the microwave technique to enhance the chemical reaction for NO removal by the microwave-discharge method, [33][34][35] such as the SCR of NO by CH 4 over Fe/HZSM-5, [33] the decomposition of NO activated by microwave discharge with no catalyst, [34] the reduction of NO by CH 4 over Co-HZSM-5, [35] and the microwave-assisted reduction method, [36][37][38][39][40] such as Fe/Ga-5A zeolite as a catalyst and NH 4 HCO 3 as a reducing agent, [36] and microwave-induced reactions of nitrogen oxides and pyrolytic carbon matrix. [37] In addition, our previous study reported the microwave catalytic reduction of NO into N 2 by Mn 2 O 3 supported on active carbon (AC) at low temperature under excess oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…Among them are the electrochemical dealloying (electrochemical leaching of the less noble component from an alloy) [12], the redox exchange of underpotential deposited Cu by e.g. Pt [9] and the direct electrodeposition of a noble metal around a pre-formed metal core [13,14].In our previous work, PtCu /CNT alloy catalysts were prepared by microwave assisted polyol synthesis and the influence of different synthesis parameters on the structure of the synthesized catalysts and their activity towards oxygen reduction reaction (ORR) was evaluated [15].During these investigations it turned out that it is a considerable challenge to prepare bimetallic nanoparticles containing Pt and Cu in a single reduction step using the polyol method, similar as reported before forPtRu and PtNi [16,17]. In continuation of these activities here we report on the synthesis of PtCu/CNT nanoparticles in a two reduction steps procedure.…”
mentioning
confidence: 87%